ANALISIS DETERMINAN RETURN SAHAM PADA PERUSAHAAN LQ 45 DI BEI PERIODE 2017-2021 - Popi Dwiyanti, (2022)
Stock return is a reward for investors' willingness to take risks, as well as their time and money. Investors frequently use fundamental factors in determining returns in determining investment decisions, such as firm value, profitability, and systematic risk. The purpose of this research is to determine the impact of firm value, profitability, and systematic risk on stock returns. This study employs a non-probability sampling technique with a saturated sample of 45 LQ 45 companies from June 2021 to January 2022. This study's sampling period is five years, from 2017 to 2021. This research technique employs panel data regression analysis as a hypothesis test, with a significance level of 0.05 (5%). According to the findings of this study, firm value as proxied by PBV and profitability as proxied by ROE have no effect on stock returns, while systematic risk has a positive effect on stock returns.